Paternal Dietary Methionine Supplementation Improves Carcass Traits and Meat Quality of Chicken Progeny - Elsharkawy, Mohamed Shafey (Animals (Basel), 2021)
SIMPLE SUMMARY: High meat quality is one of the demands made by consumers. Therefore, studies have concluded that meat quality can be improved through some feed additives to broiler diets. Other studies showed that broilers meat quality improved by adding some nutrients to the maternal diet, so this study was conducted to evaluate the paternal effects of dietary 0.1% methionine on meat quality and carcass traits of offspring. Our results suggested that paternal dietary supplementation with 0.1% methionine enhances offspring carcass eviscerated yield, thigh muscles yield and reduces abdominal fat, also meat shear force, drip loss, pH-value, and color. The expression of genes associated with meat quality support these results. ABSTRACT: The effects that maternal dietary methionine have on progeny have been reported on broilers. However, the paternal effects are not known, so the current study was conducted to explore the influences of paternal dietary methionine (Met) have on progeny carcass traits, meat quality, and related gene expressions. A total of 192 hens and 24 roosters from Ross parent stock at 36 weeks of age were selected. From week 37 to 46, the roosters were allocated to two groups with three replicates of 4 cocks each, (control, 0.28% Met), and methionine group (MET group, 0.28% Met + 0.1% coated Met). The results revealed that, although the heavier live body weight in progeny at day 49 of control group compared to MET group (p < 0.05), the relative eviscerated yield and relative thigh muscle yield were higher in MET group (p < 0.05); but the relative abdominal fat was lower (p < 0.05). In thigh and breast muscles, a positive response of pH(24 h) value, shear force (g) and drip loss (%) were observed in MET group (p < 0.05). The lightness (L) and redness (a) were increased (p < 0.05) in breast muscles of MET group, while only the redness (a*(24 h)) and yellowness (b*(24 h)) were increased (p < 0.05) in thigh muscles of MET group. The gender has a significant (p < 0.05) effect on carcass traits and muscle redness (a*), where these traits improved in males, and no interaction between treatments and gender were observed for these results. The expression levels of PRKAG2 and PRDX4 supported the changes in muscle pH, with these up-regulated in thigh and breast muscles of MET group, the PPP1R3A gene supported the changes in pH value being down-regulated (p < 0.01) in these same muscles. The BCO1 gene expression was consistent with the changes in meat color and was up-regulated (p < 0.01) in thigh muscles of MET group, consistent with the changes in b* color values. Finally, it was concluded that the supplementation of 0.1% Met to rooster diets could improve carcass characteristics and meat quality of progeny.